Non-invasive modulation of somatosensory evoked potentials by the application of static magnetic fields over the primary and supplementary motor cortices - Kirimoto, Hikari; Asao, Akihiko; Tamaki, Hiroyuki; Onishi, Hideaki (Scientific reports, 2016)
This study was performed to investigate the possibility of non-invasive modulation of SEPs by the application of transcranial static magnetic field stimulation (tSMS) over the primary motor cortex (M1) and supplementary motor cortex (SMA) and to measure the strength of the NdFeB magnetic field by using a gaussmeter. An NdFeB magnet or a non-magnetic stainless steel cylinder (for sham stimulation) was settled on the scalp over M1 and SMA of 14 subjects for periods of 15 min. SEPs following right median nerve stimulation were recorded before and immediately after, 5 min after and 10 min after tSMS from sites C3′ and F3. Amplitudes of the N33 component of SEPs at C3′ significantly decreased immediately after tSMS over M1 by up to 20%. However, tSMS over the SMA did not affect the amplitude of any of the SEP components. At a distance of 2–3 cm (rough depth of the cortex), magnetic field strength was in the range of 110–190 mT. Our results that tSMS over M1 can reduce the amplitude of SEPs are consistent with those of low-frequency repeated TMS and cathodal tDCS studies. Therefore, tSMS could be a useful tool for modulating cortical somatosensory processing.